THE IMPORTANCE OF MATHEMATICAL STATISTICS IN THE ECONOMY - Nazarov Kholmo'min Abduvahobovich (Galaxy International Interdisciplinary Research Journal, 2023)
While reading this article you will be able to get acquainted with general facts about the theme, methods and main functions of statistics. In addition to this, the writer highlighted the important points according to the economic statistics of Uzbekistan recent years.